Elements promoting learning from a strategic partner: a Malaysia case - Mansor, Zuraina (Universiti Putra Malaysia Press, 2013)
Strategic alliances (SAs) are becoming a popular and prominent strategy to help many firms sustain its competitive advantage in the rapid and unexpected global economy. This inter-organisational structure is becoming essential feature in today’s intensely competitive market as a means for facilitating market entry, acquiring new technology, leveraging economies of scale, and enhancing new product development capabilities. Additionally, in the recent trends of strategic alliance literature, they have been linked to the organisational learning literature where alliances create environments for learning and knowledge transfer. This phenomenon is referred to as ‘alliance-based learning’. The main purpose of this paper is to discuss how learning can be promoted via alliance arrangement. The study used an in-depth case study method, where a child business was set up upon the signing of strategic alliance agreement between parent partner in Malaysia with foreign parent partner from the UK, and the partnership had included learning as one of their main objectives.